Nitric Oxide for preterm infants - Manuel Sánchez Luna; Maria Luisa Franco; Elena Zamora; Belén Bernardo (Hygeia Press di Corridori Marinella, 2013)
Inhaled nitric oxide (iNO) is a selective pulmonary vasodilator that has demonstrated its efficacy when used to treat severe hypoxemic respiratory failure associated to pulmonary hypertension in term or near term newborns since 1992. Premature newborn infants are not included in the approved indication of iNO use, but in some circumstances, when pulmonary hypertension is associated to severe respiratory failure iNO has been demonstrated as an effective therapy to improve respiratory failure. Also iNO demonstrated in animal studies its potential use to treat or prevent BPD, but clinical trials have failed to demonstrate any beneficial effect of this drug when used as routine or rescue therapy, and probably only in a selected group of preterm infants, used soon after delivery and not severely ill it could have a role if any. The neuro-protective effect found in some experimental studies and clinical reports gives a new attractive potential indication of iNO use in this population, but current data of follow-up multicenter randomized controlled trials do not support this effect.   Proceedings of the 9th International Workshop on Neonatology · Cagliari (Italy) · October 23rd-26th, 2013 · Learned lessons, changing practice and cutting-edge research